Gerontological social work and cardiac rehabilitation. (9th August 2019) - Shah, Avani; Meadows, James T.; Anderson, Kimberly Granda; Raveis, Victoria H.; Scogin, Forrest; Templeton, Stacey; Simpson, Kersey; Ingram, Lee
ABSTRACT: Cardiac rehabilitation is a setting in which integrating social work services can benefit older adults. Many cardiac rehabilitation patients endorse symptoms of stress and depression following a cardiac event, impeding their ability to participate fully in cardiac rehabilitation services or recover from a heart attack. Gerontologically trained social workers can improve the care of older adults with heart disease in a variety of ways and this paper discusses the potential roles social workers can play in enhancing care. Two examples demonstrating how community academic partnerships can lead to improved options for older adults following a heart attack are discussed. First, using a microsystems approach, social workers embedded within cardiac rehabilitation may improve patient quality of life, address social service needs, provide mental health treatment, and assist in the completion of standard cardiac rehabilitation assessments. Second, using a macrosystems approach, social workers can help communities by developing partnerships to establish infrastructure for new cardiac rehabilitation clinics that are integrated with mental health services in rural areas. Social workers can serve an important role in addressing the psychological or social service needs of cardiac rehabilitation patients while increasing access to care.